JENIS ALGA COKLAT PENGHASIL ALGINAT DI PULAU AMBON - Frijona F Lokollo; Ronald D Hukubun (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2022)
Brown algae contains alginate is a hydrocolloid compound. This study aims to determine the types of brown algae as alginate producers in the coastal waters of Ambon island, Tial and Liang villages, Central Maluku. This research was conducted in April 2021. Sampling is carried out by means of free collection at low tide, at the time of sampling it is visually observed the condition of the substrate on which brown algae. Liang village beach as a whole has a variety of substrates of rocky, rocky sand, sand mixed with dead coral. However, in the sampling area, it was found that the dominant substrate was rocky sand substrate, and dead coral. Tial village beach has four types of substrates, namely rocky substrates in area A directly adjacent to the coast and have a substrate area of 2,250 m2 (15%), coral fault substrates and rocky in area B are in the littoral zone have a substrate area of 3,000 m2 (20%), sand substrates and coral faults in area C are in the littoral zone have a substrate area of 5,250 m2 (35%) coral substrates in area D are directly adjacent to the subtidal area and have a substrate area of 4,500 m2 (30%). All four substrates are in the intertidal zone. The substrates that cover the observation area a lot are sand substrates and coral faults. The results of the identification of brown algae species on the shores of Liang and Tial villages found four species classified in one division, one class, two families, and three genera. The diversity of brown algae species in the coastal waters of Tial there are three types of brown algae, Sargassum duplicatum, Turbinaria ornata, and Padina minor and on Liang beach there are two species of brown algae, Sargassum polycyctum and Padina minor. The four types of brown algae found have the potential to be a source of alginate